Ta’wîl Ibn al-Zubayr terhadap Mutashâbih al-Lafz dalam al-Qur’an - Yaumin Nahri, Delta (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2014)
The word is strung into the verses of the Koran is a divine sentence a similar level of fluency and beauty of literature between one verse with other verses. Although the Koran uses mutashâbih al-lafz and tikrâr, the choice of words is representative of the context is going on. This means that the choice of words shows the detail of information that occurred and the repetition of words not followed essentially the repetition of meaning, but brings new meaning different from the first words that are complementary and not interchangeable. This rule is brought to Ibn al-Zubayr al-Gharnâtî trough his creation, Milâk al-Ta’wîl al-Qâti’ bi Dhawi al-Ilhâd wa al-Ta’tîl fî Tawjîh al-Mutashâbih al-Lafz min Ây al-Tanzîl. This creation became a real reflection of insight cleric Granada, which uses the method applied research (al-manhâj al-tatbîqî al-tahlîlî) in every discussion. This article will explain the interpretation of Ibn Zubayr on the causes of differences in editorial verses of the Koran, known as al-lafz mutashâbih.